1999
DOI: 10.1080/009841099158051
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic Cancer Mortality and Total Hardness Levels in Taiwan's Drinking Water

Abstract: The possible association between the risk of pancreatic cancer mortality and hardness levels in drinking water from municipal supplies was investigated in a matched case-control study in Taiwan. All eligible pancreatic cancer deaths (883 cases) of Taiwan residents from 1990 through 1994 were compared with deaths from other causes (883 controls), and the hardness levels of the drinking water used by these residents were determined. Data on water hardness throughout Taiwan was collected from Taiwan Water Supply … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…The significance of both elements in drinking water for cardiovascular diseases has been documented many times in academic literature, mainly for the association of Ca and Mg deficits and increased incidence or mortality rates for CVD [21,22,23,24]. However, there are very few works linking the incidence or mortality rates of OD with Ca and Mg deficiency in drinking water [25,26,27,28,29,30,53]. Nriagu et al link increased carcinogenity of desalinated water with electrolyte disturbance and hypomagnesemia [54].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The significance of both elements in drinking water for cardiovascular diseases has been documented many times in academic literature, mainly for the association of Ca and Mg deficits and increased incidence or mortality rates for CVD [21,22,23,24]. However, there are very few works linking the incidence or mortality rates of OD with Ca and Mg deficiency in drinking water [25,26,27,28,29,30,53]. Nriagu et al link increased carcinogenity of desalinated water with electrolyte disturbance and hypomagnesemia [54].…”
Section: Discussionmentioning
confidence: 99%
“…There are many publications documenting increased incidence and mortality rates for cardiovascular diseases associated with a deficit of Ca and Mg in drinking water [18,19,20,21,22,23,24]. Several studies can be found that link these deficits to increased mortality from oncological diseases as well [25,26,27,28,29,30]. As of yet, there is no documentation of the influence of Ca and Mg deficiency in drinking water on the respiratory and gastrointestinal systems.…”
Section: Introductionmentioning
confidence: 99%
“…Rather, drinking water calcium plays a key role in a number of physiological functions like suppression of neuromuscular excitability, myocardial function, heart and muscle contractility, intracellular information transmission and blood coagulation (Kozisek, 2005). Consequently, the outcome of numerous cohort studies recommended that water hardness may protect against many diseases particularly against cardiovascular diseases (Yang et al, 1996), cerebrovascular diseases (Yang et al, 1998), cancer of esophagus (Yang et al, 1999c), cancer of pancreas (Yang et al, 1999d), cancer of rectum (Yang et al 1999e) and breast cancer (Yang et al, 2000). Drinking water calcium has also proven to be statistically significant in reducing the risk for pre-term birth and low birth weight (Yang et al, 2002).…”
Section: +mentioning
confidence: 99%
“…Subjects who died from malignant neoplasm of esophagus (code 150) (Yang et al, 2002), stomach (code 151) , colon (code 153) (Yang et al, 1997), rectum (code 154) (Yang & Chiu, 1998), pancreas (code 157) (Yang et al, 1999b), breast (code 174) (Yang et al, 2000b), ovary (code 183) (Chiu et al, 2004), and prostate (code 185) (Yang et al, 2000a) and from those who died from cardiovascular disease (codes 410-414) (Yang et al, 1996), cerebrovascular diseases (codes 430-438) (Yang, 1998), diabetes mellitus (code 250) (Yang et al, 1999a), and hypertension (codes 401-405) (Yang & Chiu, 1999) were also excluded from the control group because of previously reported negative correlations with hardness (calcium or magnesium) levels in drinking water. Control subjects were pairmatched to the cancer cases by gender, year of birth, and year of death.…”
Section: Study Area and Subject Selectionmentioning
confidence: 99%